1996
DOI: 10.1136/bmj.312.7031.601
|View full text |Cite
|
Sign up to set email alerts
|

A major outbreak of asthma associated with a thunderstorm: experience of accident and emergency departments and patients' characteristics

Abstract: This study supports the view that this epidemic was larger than previously reported epidemics and the hypothesis that "thunderstorm associated asthma' is related to aeroallergens. Demands on resources were considerable; a larger proportion of patients needing intensive care would have caused greater problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 15 publications
0
33
1
Order By: Relevance
“…The rupture of pollen grains due to an osmotic shock during thunderstorms or under especially wet conditions has been studied. Suphioglu et al [37] and Davidson et al [38] confirmed that after strong storms, there were notable asthmatic epidemics due to the osmotic rupture of the Poaceae pollen grain, which releases starch granules ranging in size from 2.5 to 0.6 µm into the atmosphere. In 2002, Taylor et al [39] observed in the laboratory that grass anthers under various meteorological conditions are a site of pollen rupture and a source of fine particulate aerosols that contain pollen allergens.…”
Section: Discussionmentioning
confidence: 56%
“…The rupture of pollen grains due to an osmotic shock during thunderstorms or under especially wet conditions has been studied. Suphioglu et al [37] and Davidson et al [38] confirmed that after strong storms, there were notable asthmatic epidemics due to the osmotic rupture of the Poaceae pollen grain, which releases starch granules ranging in size from 2.5 to 0.6 µm into the atmosphere. In 2002, Taylor et al [39] observed in the laboratory that grass anthers under various meteorological conditions are a site of pollen rupture and a source of fine particulate aerosols that contain pollen allergens.…”
Section: Discussionmentioning
confidence: 56%
“…It is likely that the proportions of daily asthma events (hospitalisations, etc) attributable to aeroallergen exposure are likely to be small. However, analyses of asthma epidemics occurring during thunderstorms [33][34][35][36][37][38] and the unloading of soya beans in Barcelona 39 suggest that aeroallergens can play a significant role in precipitating asthma attacks. Furthermore, studies have linked the magnitude of the effects of fungal spores to asthma severity in subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Several patients who were examined, who were not known to be asthmatics or were affected only by seasonal rhinitis, experienced an asthma attack [50-52]. During a 30-h period from 6 p.m. on June 24, 1994, 640 patients with asthma or other airways disease (283 of whom were not known to be asthmatic and 403 were affected only by seasonal rhinitis) attended several emergency departments, nearly 10 times the expected number of 66 patients.…”
Section: Introductionmentioning
confidence: 99%